IN SILICO ANALYSIS AND DOCKING STUDY OF THE ACTIVE PHYTO COMPOUNDS OF MORINGA OLEIFERA AGAINST MARBURG VIRUS VP35 PROTEIN - CHAVAN, SHIVAM; WANARASE, SHUBHAM; SHARMA, SAMEER (Innovare Journal of Sciences, 2022)
Objective: Marburg is a transmissible disease of the Filoviridae family. It infected a million people worldwide. Hence, an attempt was made to identify natural compounds from Moringa oleifera, having multiple medicinal values in Indian Ayurveda, to prevent the disease, using molecular docking, drug likeness prediction, absorption, distribution, metabolism, and excretion (ADME) analysis, and toxicity prediction. Methods: Marburg main protein was retrieved from the protein data bank database. The ligands with poor binding and molecules that can affect docking were removed and docking is done with the PyRx tool. ADME and drug-likeness analysis were done using Swiss-ADME and absorption, distribution, metabolism, excretion, and toxicity (ADMET) lab web server. Results: Ramachandran plot analysis shows the statistical distribution of the combinations of the backbone dihedral angles ϕ and ψ of the protein. Molecular docking studies show three compounds from M. oleifera have potential binding affinity to resist the main protein VP35 by preventing proteolytic cleavage, translation, and replication of the virus. ADMET profile and drug likeness and toxicity prediction showed that all three compounds Melanin, Diclazuril, and Tifentai were safe and possess drug-like properties. Conclusion: The present study suggests that Melanin, Diclazuril, and Tifentai have significant binding affinity and they could inhibit the main protein VP35 and also helps to manage the therapeutic strategies against Marburg Virus.